2017
DOI: 10.3354/aei00224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light source and intensity on sexual maturation, growth and swimming behaviour of Atlantic salmon in sea cages

Abstract: We investigated how highly efficient LED light sources may be used in Atlantic salmon cage farming. Specifically, we tested the incidence of sexual maturation and growth patterns in autumn sea-transferred Atlantic salmon Salmo salar L. during their second sea winter given continuous artificial light (LL) (between 13 January and 18 June) of 5 different intensities using LED sources, compared to a single intensity provided by a metal halide (MH) source or a control treatment of natural light (NL). Growth effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
4
11
0
1
Order By: Relevance
“…Results of the study demonstrated that using an artificially prolonged photoperiod improved growth and retarded the sexual maturation of brook trout. Changes in growth rate are consistent with earlier studies showing that continuous artificial light has a growth-promoting (Hansen, Fjelldal, Folkedal, Vagseth, & Oppedal, 2017;Önder et al, 2016;Taylor, Migaud, Porter, & Bromage, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of the study demonstrated that using an artificially prolonged photoperiod improved growth and retarded the sexual maturation of brook trout. Changes in growth rate are consistent with earlier studies showing that continuous artificial light has a growth-promoting (Hansen, Fjelldal, Folkedal, Vagseth, & Oppedal, 2017;Önder et al, 2016;Taylor, Migaud, Porter, & Bromage, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Results of the study demonstrated that using an artificially prolonged photoperiod improved growth and retarded the sexual maturation of brook trout. Changes in growth rate are consistent with earlier studies showing that continuous artificial light has a growth‐promoting effect on salmonids (Hansen, Fjelldal, Folkedal, Vagseth, & Oppedal, ; Önder et al, ; Taylor, Migaud, Porter, & Bromage, ).The growth stimulation has not been shown affected by an increase in the feeding period, but by increase of daylight hours per se (Taylor, North, Porter, Bromage, & Migaud, ). Randall, North, Futter, Porter, and Bromage () also reported growth‐enhancing effects of continuous artificial lighting in rainbow trout without additional feed.…”
Section: Discussionsupporting
confidence: 90%
“…Slack current conditions of 4 cm s -1 , on the other hand, resulted in higher lipid content in the muscle compared to post-smolt kept at moderate currents of 18 cm s -1 (Solstorm et al 2015). Nevertheless, this may not be relevant for salmon in commercial cages where salmon frequently display daytime schooling with swimming speeds of > 0.5 fish length s −1 (Oppedal et al 2011, Hansen et al 2017). Atlantic salmon have been observed to sustain 80% of U crit for at least 4 h (Hvas & Oppedal 2017).…”
Section: Classification and Site Suitabilitymentioning
confidence: 96%
“…In Norway, sea temperatures generally start to rise in March and decrease in August, which somewhat lags behind photoperiod, whereby the minimum is in December and maximum in June. Photoperiod is a strong regulator of swimming behavior, growth and sexual maturation in the host fish (Taranger et al 2010, Hansen et al 2017. While a few studies have explored the effect of light on hatching, swimming behavior and infection success in salmon lice (Boxaspen & Naess 2000, Flamarique et al 2000, Browman et al 2004, little is known about the effects of photoperiod on development.…”
Section: Introductionmentioning
confidence: 99%